A Destituição Do Poder Familiar: Os efeitos sociais da lei 12.010/2009 na vida de mulheres pobres na cidade de Niterói - Barros, Maria Izabel Valença (2014)
In August 2009, the Law 12.010/2009, which deals with family and community life for children and adolescents was introduced in our legal system significantly modifying the Statute of Children and Adolescents and the Civil Code. The aforementioned law is presented with the aim of contributing a new look at the adoption process. However, as this is a recent rule of law which seeks to change a pre-existing structure, little is known about its practical aspects in everyday reality and its effects on the lives of poor women who suffer with the perspective of losing the family power. Thus, this study seeks to analyze the ramifications of this legislation and its effects on the lives of poor women in Niterói, from the look of the legal professionals. In this way, we had as research field the concentrated hearings as well as the conducting semi-structured interviews with the operators of law. The conclusions of this study indicate: 1) to the permanence of a sexist bias, which often confirms discrimination and exclusion; 2) that poverty has been a decisive factor in the loss of family power; 3) the need for greater interdisciplinary and intersectoral coordination for building an effective networking; 4) the need to rebuild a look at host institutions recognizing them for their contradictoriness and 5) the need for continued capacity building